EDUCAÇÃO ESPECIAL E INCLUSIVA NA FORMAÇÃO DOCENTE: ANÁLISE DOS PPCs DOS CURSOS DE LICENCIATURA EM MÚSICA DAS UNIVERSIDADES FEDERAL E ESTADUAL DO MARANHÃO - SILVA, Isabele Ferreira da (2024)
This master's thesis presents the results of the critical/analytical study of the Pedagogical Projects of the Music Degree Courses (abbreviation in Portuguese: PPCs) at the Universidade Federal do Maranhão (UFMA) and the Universidade Estadual do Maranhão (UEMA). In this sense, its specific objectives include dealing with people who present different profiles and situations; to analyze the documents that determine the implementation of contemporary education and the implementation of basic education, with a focus on teaching Art/Music; and signal the paths of teaching music in the special/inclusive context contained in the PPCs of the Courses offered by the universities. This theme is justified by the need to reflect on the training of music educators considering their skills, to be developed subsequently. In this context, the Research Problem asks: How do the Pedagogical Projects of the Music Degree Courses at UFMA and UEMA correspond to the realities of the public in special/inclusive education (abbreviation in Portuguese: EEI)? It was raised as a hypothesis that the PPCs of the Courses require greater interaction between the disciplines and specialist teachers, considering the implementation and implementation documents, aimed at teaching music. The methodology refers to a qualitative approach in line with documentary research and comparative study, regarding its procedures. Its theoretical foundation is substantiated in international documents (UNESCO, 1990, 1994, 2002; ISME, 2023; Fladem, 2023) and national legislation (Brasil, 1990, 1996, 2015) on the implementation of contemporary education, with a focus on teaching Art /Music, in addition to the national basic education implementation documents (Brasil, 1997, 1998a, 1998b, 2000, 2018; ABEM, 2023). As well as authors who defend teaching music for everyone (Brasil, 2015, 2018; Trindade, 2008), among others. The results indicate that the three PPCs analyzed – two from UFMA (Campus São Luís and Campus São Bernardo) and one from UEMA (Campus São Luís) – highlighted some connections on the topic of EEI at different levels and depths: such as offering subjects in mandatory and optional modes, in addition to developing complementary themes that can be discussed in the classroom, at the discretion of teachers and students. However, it was observed in the curriculum that their bibliographical references were often out of date, not in agreement with the syllabus and insufficient, needing to be intensified, expanded, and strengthened in terms of their skills to be developed, focused on professional training and music teaching at the public in focus. Furthermore, it was found that in none of the three Courses was the sufficient workload considered for the training of music teachers to work in basic education with the Special/Inclusive Education public.